Engaging and empowering youth work professionals in Malaysia - Ismail, Ismi Arif (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The focus on youth development, the launching of the 6 Youth Development Initiatives which transpire from the National Youth Laboratory and the 1M4U project, provided an impact on the Malaysian youth. The country’s current focus is about empowering youth and unleashing their potentials. The biggest challenge at present is to ensure that they are surrounded by the able youth work professionals who have the capacity and capability to support these efforts and ultimately transform this vision into a reality. This paper will review and address a number of significant points namely, (i) challenges and strategies to develop and retain talents into the youth work sector, (ii) efforts in changing the youth work professionals’ mindset, (iii) indexing relevant knowledge and skills of youth work professionals, (iv) strategizing how both the youth work experts, higher education and research institutions and HRD professionals can collaborate as partners in the human resource development of youth work professionals, and (v) projecting future of and challenges to the HRD in youth work in Malaysia. It is believed that addressing these significant points will help us to engage and empower youth work professionals to ultimately engage and empower Malaysian youths as partners in nation building.